Wypowiedzi świadków historii w perspektywie historycznej i językoznawczej. Analiza wybranych relacji ludzi ze znakiem „P” - Bekieszczuk, Krzysztof; Rosner-Leszczyński, Kacper (2022)
The article presents a study of historical and linguistic aspects of testimonies of history witnesses. In our case those were forced labourers – Poles obliged in the Third Reich to wear the “P” symbol indicating their ethnicity. Because of the nature of the topic, an interdisciplinary approach was necessary. The first part of the paper recalls briefly the history of forced labour in Germany during World War 2 as well as illustrates with some examples the everyday life difficulties of the workers. All the samples analysed in this study are taken from an anthology by Anna Kosmulska, who collected and published them twice in 1995 and 2020 (2nd revised and expanded edition). It is an interesting fact that many of the people with the “P” symbol decided to stay after the war in the region and the city where they were forced to work for Germans. The article tries to find traces of orality in the redacted text of primordially spoken testimonies. To investigate that we decided to apply the theory of five indicators of spoken language by Bartmiński and Niebrzegowska-Bartmińska as well as certain statistical analyses (including sentence length, the relation between Polish conjunction i and preposition w, FOG index). Moreover, we discuss the communication situation of the witnesses of history together with the question of the existence of discourse community within this group and analyse the keywords of their testimonies.
Keywords: people with the “P” symbol; forced labour; oral history; witnesses of history; pragmatics; stylistics